Mixing Rules Formulation for a Kinetic Model of the Langmuir-Hinshelwood Semipredictive Type Applied to the Heterogeneous Photocatalytic Degradation of Multicomponent Mixtures - John Wilman Rodriguez-Acosta; Miguel Ángel Mueses; Fiderman Machuca-Martínez (International Journal of Photoenergy)
Mixing rules coupled to a semipredictive kinetic model of the Langmuir-Hinshelwood type were proposed to determine the behavior of the heterogeneous solar photodegradation with TiO2-P25 of multicomponent mixtures at pilot scale. The kinetic expressions were expressed in terms of the effective concentration of total organic carbon (xTOC). An expression was obtained in a generalized form which is a function of the mixing rules as a product of a global contribution of the reaction rate constant k′ and a mixing function fC. Kinetic parameters of the model were obtained using the Nelder and Mead (N-M) algorithm. The kinetic model was validated with experimental data obtained from the degradation of binary mixtures of chlorinated compounds (DCA: dichloroacetic acid and 4-CP: 4-chlorophenol) at different initial global concentration, using a CPC reactor at pilot scale. A simplex-lattice {2,3} design experiment was adopted to perform the runs.